A PHENOMENON OF CONTRAST IN SPEAKING AND WRITING SKILLS OF INDONESIAN SEAFARERS - Maru, Mister Gidion; Ratu, Noviana Neila (SoCul: International Journal of Research in Social Cultural Issues, 2024)
This research explores the phenomenon of contrast between speaking and writing skills in English among Indonesian seafarers, focusing on their professional experiences and the challenges they face. The study aimed to examine the frequency of use of the English language, the difficulties experienced in speaking and writing, and the strategies used to improve these skills. With a qualitative approach, data was collected through video call interviews with 10 Indonesian seafarers working on various ships abroad. Thematic analysis is used to identify patterns and themes that emerge from the data. The results of the study showed that most sailors felt more confident in speaking English. Because Speaking skills are more commonly practiced and are considered less challenging, although difficulties still arise, especially when communicating with native speakers due to accent and speed of speech. In contrast, writing in English is considered more complex, requiring careful attention to correct writing. The study concludes that special training support is needed for Indonesian seafarers to be able to develop their English skills, both speaking and writing. The study also highlights the importance of upskilling-based training to address this gap, such as English language courses and writing training focused on the needs of the maritime sector. This study suggests that Indonesian seafarers be given more structured training to improve these two skills to improve the quality of communication in the international work environment and also this program can improve their communication competence, thereby supporting efficiency and effectiveness in the global maritime environment.